Renal effects of guideline‐directed medical therapies in heart failure: a consensus document from the Heart Failure Association of the European Society of Cardiology. (27th March 2022) - Mullens, Wilfried; Martens, Pieter; Testani, Jeffrey M.; Tang, W.H. Wilson; Skouri, Hadi; Verbrugge, Frederik H.; Fudim, Marat; Iacoviello, Massimo; Franke, Jennifer; Flammer, Andreas J.; Palazzuoli, Alberto; Barragan, Paola Morejon; et al.
Abstract: Novel pharmacologic treatment options reduce mortality and morbidity in a cost‐effective manner in patients with heart failure (HF). Undisputedly, the effective implementation of these agents is an essential element of good clinical practice, which is endorsed by the European Society of Cardiology (ESC) guidelines on acute and chronic HF. Yet, physicians struggle to implement these therapies as they have to balance the true and/or perceived risks versus their substantial benefits in clinical practice. Any worsening of biomarkers of renal function is often perceived as being disadvantageous and is in clinical practice one of the most common reasons for ineffective drug implementation. However, even in this context, they clearly reduce mortality and morbidity in HF with reduced ejection fraction (HFrEF) patients, even in patients with poor renal function. Furthermore these agents are also beneficial in HF with mildly reduced ejection fraction (HFmrEF) and sodium–glucose cotransporter 2 (SGLT2) inhibitors more recently demonstrated a beneficial effect in HF with preserved ejection fraction (HFpEF). The emerge of several new classes (angiotensin receptor–neprilysin inhibitor [ARNI], SGLT2 inhibitors, vericiguat, omecamtiv mecarbil) and the recommendation by the 2021 ESC guidelines for the diagnosis and treatment of acute and chronic HF of early initiation and titration of quadruple disease‐modifying therapies (ARNI/angiotensin‐converting enzyme inhibitor + beta‐blocker + mineralocorticoid receptor antagonist and SGLT2 inhibitor) in HFrEF increases the likelihood of treatment‐induced changes in renal function. This may be (incorrectly) perceived as deleterious, resulting in inertia of starting and uptitrating these lifesaving therapies. Therefore, the objective of this consensus document is to provide advice of the effect HF drugs on renal function.